2020
DOI: 10.3892/or.2020.7507
|View full text |Cite
|
Sign up to set email alerts
|

Single‑cell RNA sequencing of t(8;21) acute myeloid leukemia for risk prediction

Abstract: Single-cell RNA sequencing (scRNA-seq) of bone marrow or peripheral blood samples from patients with acute myeloid leukemia (AML) enables the characterization of heterogeneous malignant cells. A total of 87 cells from two patients with t(8;21) AML were analyzed using scRNA-seq. Clustering methods were used to separate leukemia cells into different sub-populations, and the expression patterns of specific marker genes were used to annotate these populations. Among the 31 differentially expressed genes in the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…One particularly studied blood cancer using scRNA-seq is acute myeloid leukemia (AML), a malignancy derived from myeloid hemopoietic cells that has a high relapse rate and overall poor outcome following standard chemotherapy regimens ( Yilmaz et al, 2019 ). Xiong et al (2020) used the Fluidigm C1 platform to study at the single-cell level the bone marrow of two AML patients. Of the 31 differentially expressed genes in the AML cells of the patient who relapsed after hematopoietic stem cell transplantation, the authors found three cancer genes ( ARID2 , MLL , and SYNCRIP ) that served as prognostic biomarkers in a validation cohort of 52 AML patients analyzed by bulk RNA-seq.…”
Section: Hematologic Malignanciesmentioning
confidence: 99%
“…One particularly studied blood cancer using scRNA-seq is acute myeloid leukemia (AML), a malignancy derived from myeloid hemopoietic cells that has a high relapse rate and overall poor outcome following standard chemotherapy regimens ( Yilmaz et al, 2019 ). Xiong et al (2020) used the Fluidigm C1 platform to study at the single-cell level the bone marrow of two AML patients. Of the 31 differentially expressed genes in the AML cells of the patient who relapsed after hematopoietic stem cell transplantation, the authors found three cancer genes ( ARID2 , MLL , and SYNCRIP ) that served as prognostic biomarkers in a validation cohort of 52 AML patients analyzed by bulk RNA-seq.…”
Section: Hematologic Malignanciesmentioning
confidence: 99%